The Effectiveness of the Story Method in Increasing the Spiritual Intelligence of the Blind - Risma Septiani Wahyu Kurnia; Kusnadi; Emi Puspita Dewi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is entitled The Effectiveness of the Story Method in Improving the Spiritual Intelligence of Blind People. This research is motivated by the limitations of blind people to mobility and access to religious knowledge which causes low spiritual intelligence so that it has an impact on the psychological and spiritual emptiness of blind people. The purpose of this study was to determine the effectiveness of the story method in improving the spiritual intelligence of blind people. This study used a quantitative research method with a Quasi Experimental research design with a Nonequivalent Control Group Design model that divides two groups, namely the experimental group and the control group. Testing is done using simple linear regression analysis. The results of this study indicate that the t test (partial test) obtained a t value of 3.196> 0.514 and a sig value of 0.007 <0.05 and the results of the R square determination analysis of 0.440 which means that the percentage of the influence or effectiveness of the story method in improving spiritual intelligence is 44% and 56% is influenced by other variables not discussed in this study. Based on these results, it is concluded that Ha is accepted and H0 is rejected, so there is an effectiveness of the story method in improving the spiritual intelligence of blind people.